Use of self-administered wireless home digital cardiotocograph in pregnant women at risk for premature birth - Lind, Jolline (2024)
At present, there is no agreement on the effectiveness of home monitoring of fetal heart rate and uterine contractions through self-administered cardiotocography in pregnant women at risk for premature birth. This method is controversial, requiring additional research to demonstrate its real value. The objective was to evaluate the association between variations in self-applied wireless home mobile digital cardiotocography and premature birth. From August 2021 until July 2022, 75 pregnant women with at least one risk factor for premature birth underwent external monitoring of uterine contractions and fetal heart rate, from the 28th week until delivery, daily, for 20 minutes, using a self-applied wireless home digital cardiotocograph. The test was considered positive when it presented a suspicious or abnormal result according to the Fischer Scale. The incidence of premature births was 16%. The method revealed a sensitivity of 81.82%, a negative value of 93.55% and an AUC of 73.7%. It is concluded that a negative test is associated with a low risk of premature birth. However, in the face of a positive test, it is necessary to associate it with other markers of premature birth to improve recognition of patients at high risk.